The camping trip - Mann, Jennifer K. (Candlewick Press, 2020)
Ernestine is beyond excited to go camping. She follows the packing list carefully (new sleeping bag! new flashlight! special trail mix made with Dad!) so she knows she is ready when the weekend arrives. But she quickly realizes that nothing could have prepared her for how hard it is to set up a tent, never mind fall asleep in it, or that swimming in a lake means that there will be fish -- eek!
Keywords: Girls / Juvenile fiction; Camping / Juvenile fiction; Filles / Romans, nouvelles, etc. pour la jeunesse; Camping / Romans, nouvelles, etc. pour la jeunesse; Camping; Girls; Fiction; Juvenile works; Bilderbuch